Android-Based Application for Supporting Aerobic Exercise of Mosesahi Gymnastics - Pomatahu, Aisah R. (International Journal of Psychosocial Rehabilitation, 2020)
Mosesahi gymnastics is physical exercises developed from aerobic exercises in 2015 to increase lung capacity and cardiovascular ability. The criteria mentioned in Law No. 3 Year 2005 Article 19 Paragraph 1 on recreational sport applies to Mosesahi gymnastics, being exercises that are performed as part of the process to regain health and fitness. Performing fitness exercises requires the presence of an instructor or guide who possesses the knowledge and skills to perform fitness exercises. The aim of this article is to explain theoretically the possibility of developing a design for an Android-based Mosesahi gymnastics application.